THE LEVEL OF MANIFESTATION OF INDICATORS OF GENERAL PHYSICAL FITNESS AMONG YOUNG WEIGHTLIFTERS 10-12 YEARS OLD (World Science, 2021)
Purpose: to reveal the level of physical development and special physical fitness of weightlifters 10-12 years. Materials and Methods: In this study, young men aged 10-12 took part in weight lifting sections at the Children's Sports School of Khartsyzsk Children's Sports School, as well as in the sport boarding school No. 2 in Kharkov. The experiment involved 48 youths engaged in weightlifting. Results: show that young weightlifters who were involved in 2 stages of pedagogical experiment, stage 1 (10 - 11 years), stage 2 (11 - 12 years) - data. The revealed differences in the intensity of the increase in the indices of physical development over a two-year period of observations reflect the unevenness and heterochronicity of the maturation of the children's organism. Even with such a relatively short period of time (two years), there is a marked difference in the intensity of the increase in the majority of the studied indicators of physical development. Conclusions: The material outlined in this publication shows that physical development, special physical fitness of modern boys aged 10-12, trained in DYUSS, according to most indicators correspond to the peers of the nineties. These facts indicate a slowing down of the processes of deceleration of the physical development of modern children. This is also evidenced by the dynamics of the indicators of special physical capacity. For the absolute values of the special physical capacity of the subjects, an increase is established for the entire biennium. However, the magnitude of the relative intensity of the increase in the absolute values of the special physical capacity at differen stages of observation is different: the first year - 10,48%, the second - 0,86% (p